Illumination-driven Mesh Reduction for Accelerating Light Transport Simulations - Reich, Andreas; Günther, Tobias; Grosch, Thorsten (Computer Graphics Forum, 2015)
Progressive light transport simulations aspire a physically-based, consistent rendering to obtain visually appealing illumination effects, depth and realism. Thereby, the handling of large scenes is a difficult problem, as in typical scene subdivision approaches the parallel processing requires frequent synchronization due to the bouncing of light throughout the scene. In practice, however, only few object parts noticeably contribute to the radiance observable in the image, whereas large areas play only a minor role. In fact, a mesh simplification of the latter can go unnoticed by the human eye. This particular importance to the visible radiance in the image calls for an output-sensitive mesh reduction that allows to render originally out-of-core scenes on a single machine without swapping of memory. Thus, in this paper, we present a preprocessing step that reduces the scene size under the constraint of radiance preservation with focus on high-frequency effects such as caustics. For this, we perform a small number of preliminary light transport simulation iterations. Thereby, we identify mesh parts that contribute significantly to the visible radiance in the scene, and which we thus preserve during mesh reduction.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Categories and Subject Descriptors (according to ACM CCS); I.3.7 [Computer Graphics]: Computer Graphics - Three-Dimensional Graphics and Realism - Ray tracing